A limnological assessment of the diverse waterscape in the Cordillera Vilcanota, Peruvian Andes. Issue 3 (3rd July 2019) - Michelutti, Neal; Tapia, Pedro M.; Labaj, Andrew L.; Grooms, Christopher; Wang, Xiaowa; Smol, John P.
ABSTRACT: The Cordillera Vilcanota in the Cusco region of Peru is experiencing dramatic environmental changes due to recent warming. An understudied component of this mountain range is the diverse waterscape, which serves as a vital water source to cities and communities downstream and is critical to supporting the region's rich biodiversity. A survey of 19 sites comprising lakes, ponds, proglacial systems, and a glacial meltwater stream produced 3 main findings. First, the study sites recorded large gradients in key limnological variables including pH, specific conductivity, nutrients, and dissolved organic carbon within a relatively small area (<800 km 2 ). Second, concentrations of some metals were unexpectedly high, exceeding guidelines for the protection of aquatic life in about one-third of the study sites. Third, temperature data recorded over 1 year showed that the lakes were generally isothermal with only short periods of weak thermal stratification. Most of the limnological variability was linked to the size of the waterbody (i.e., lake or pond) and whether or not the site is connected to a glacial watershed. These baseline data are critical to assessing the limnological response to ongoing climate changes and future stressors such as mining operations and the ever-increasing demand for water.